Metamorfoses de A Reprodução: um olhar atualizado a partir da realidade portuguesa - Melo, Benedita Portugal e (2021)
This article seeks to discuss the extent to which Reproduction (Bourdieu and Passeron, 1970), 50 years after it was published, remains current for the analysis of the relations between social space and the educational system in Portuguese society. To this end, we summarize the results of recent research carried out in Portugal in the field of Sociology of Education, illustrating the communicating vessels that they establish with the referential framework of this work. We will give an account of the ways in which social classes relate to the educational system, emphasizing approximations and deviations from the matrix of French authors. We will discuss the advances, contradictions and shortcomings of compensatory education. We will conclude by the timeliness of Reproduction, but under conditions and adaptations, generating new horizons of inquiry that allow us to reconstruct the theory without destroying it. Although there is ample empirical abundance that proves the transmutation of family-based social inequalities into school inequalities and these, again, into social inequalities, we find that there are changes that come from the educational policies and the feminization of school access and success. We suggest an investment in research that promotes the articulation between observation scales (micro, meso and macro) and the intersection and consubstantiality of social inequalities (class, gender and ethnicity).